5-{2-[(2-Hydroxy-5-methylphenyl)(phenyl)methyleneamino]phenyliminomethyl}pyrrole-2-carbaldehyde - Ge Liu; Jianhui Wang; Liqin Guo; Wen-Juan Ruan (Acta Crystallographica Section E, 2008)
The title compound, C26H21N3O2, is an unsymmetrical tetradentate Schiff base ligand. The hydroxy group forms an intramolecular O—H...N hydrogen bond with an adjacent N atom. An intermolecular N—H...O hydrogen bond creates centrosymmetric dimers in the crystal packing.